Effect of Traditional Chinese Medicine directional drug penetration therapy combined with elastic bandage compression dressing on relief of ecthyma syndromes (中医定向透药联合弹力绷带加压包扎对臁疮中医证候的改善作用) - GONG Wenjing (龚文静); LYU Lili (吕丽丽) (中西医结合护理)
Objective To analyze the effect of Traditional Chinese Medicine(TCM) directional drug penetration therapy combined with elastic bandage compression dressing on relief of TCM syndrome in patients with ecthyma. Methods A total of 80 hospitalized patients with ecthyma were divided into two groups according their hospital admission sequence. In the control group(n=40), the ulcer wound was treated with elastic bandage after conventional dressing change. In the observation group(n=40), the ulcer wound was treated with directional drug penetration therapy for 15-20 minutes before dressing change, and then the ulcer wound was treated with elastic bandage after conventional dressing change. The improvement rate of ecthyma-related syndromes was measured and compared between the two groups. Results The total effective rate of syndromes relief was 97. 50%(39/40)in the observation group, which was significantly higher than 80. 00%(32/40)in the control group (P＜0. 05). Conclusion TCM directional drug penetration therapy combined with elastic bandage compression dressing has significant effect on relief of ecthyma-related clinical syndromes, and it is an easy-to-use, safe and painless TCM technique, which is worthy for clinical application. (目的 分析中医定向透药联合弹力绷带加压包扎对促进臁疮患者中医证候改善的效果。方法 根据入院时间顺序, 将住院治疗的80例臁疮患者分为两组。对照组40例患者溃疡创面采用常规换药后用弹力绷带加压包扎; 观察组40例患者在换药前进行定向透药治疗15~20 min, 溃疡创面采用常规换药后用弹力绷带加压包扎。比较两组患者臁疮相关中医证候的改善情况。结果 观察组中医证候改善总有效率97. 50%(39/40), 高于对照组的80. 00%(32/40), 差异有统计学意义(P＜0. 05)。结论 中医定向透药联合弹力绷带加压包扎能够促进臁疮患者中医证候改善, 且操作简便、安全、无痛苦, 适合临床推广使用。)